Education about School Health at SDN Sukamenteri 1-2 Garut Kota District - Iwan Shalahuddin; Udin Rosidin; Umar Sumarna; Nina Sumarni; Mamat Lukman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The perspective in school health nursing is how to integrate the concept of health in the school curriculum through efforts in early discovery related to health problems, health maintenance efforts and the school environment. School health nurses play a role in implementing EPSDT (Early and Periodic Screening, Diagnosis and Treatment of health problems). According to the Ministry of Health, UKS is an integrated effort in order to improve the ability to live a healthy life which then forms healthy behaviors of school-age children who are in school. UKS plays a role in providing knowledge related to health problems to students / children so that in the future it is hoped that they can practice a healthy lifestyle anywhere. The purpose of education is to provide and improve students' understanding of the importance of preventing health problems and to identify the importance of early detection to avoid health problems. The method used is the lecture method, question and answer, discussion and demonstration. The results of the health counselling activities were approximately 323 students. The counseling participants looked enthusiastic when the material was given. Participants participated in the counselling happily because the counselling was carried out in a fun way. The counselling activity was conducive because the participants paid attention to the material presented well. This is evidenced by the number of participants who are interested in answering questions during the question and answer session. Participants participated in the counselling happily because the counselling was carried out with a pleasant face-to-face method. The counselling activity was conducive because the participants paid attention to the material presented well about degree of school health.